Understanding Broadband over Power Line - Held, Gilbert (CRC Press, 2009)
Understanding Broadband over Power Line explores all aspects of the emerging technology that enables electric utilities to provide support for high-speed data communications via their power infrastructure. This book examines the two methods used to connect consumers and businesses to the Internet through the utility infrastructure: the existing electrical wiring of a home or office; and a wireless local area network (WLAN) access point.